Nanomechanical Infrared Spectroscopy with Vibrating Filters for Pharmaceutical Analysis. Issue 14 (7th March 2017) - Kurek, Maksymilian; Carnoy, Matthias; Larsen, Peter E.; Nielsen, Line H.; Hansen, Ole; Rades, Thomas; Schmid, Silvan; Boisen, Anja
Abstract: Standard infrared spectroscopy techniques are well‐developed and widely used. However, they typically require milligrams of sample and can involve time‐consuming sample preparation. A promising alternative is represented by nanomechanical infrared spectroscopy (NAM‐IR) based on the photothermal response of a nanomechanical resonator, which enables the chemical analysis of picograms of analyte directly from a liquid solution in only a few minutes. Herein, we present NAM‐IR using perforated membranes (filters). The method was tested with the pharmaceutical compound indomethacin to successfully perform a chemical and morphological analysis on roughly 100 pg of sample. With an absolute estimated sensitivity of 109±15 fg, the presented method is suitable for ultrasensitive vibrational spectroscopy. Abstract : Nanomechanical resonators for IR spectroscopy : Perforated silicon nitride membranes can be used as porous filters for sampling picograms of analyte simply nebulized from a dispersion. Measuring the resonance frequency of such structures irradiated with IR light allows obtaining IR spectra of a given compound. Indomethacin was studied using this method in proof‐of‐concept experiments.